DETERMINATION OF ANDROSTERONE FROM CELERY BY A NEW VALIDATED LC-MS/MS METHOD - SIMEDRU, Dorina; NAGHIU, Anca; CADAR, Oana; DORDAI, Marius Lucian; LUCA, Emil; SIMON, Ioan (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Celery is recently the subject of various studies due to its role in human nutrition and for medicine purposes. One of the most speculated ideas is that celery contains high quantities of androsterone which makes it suitable for infertility treatments. Due to this trend, the purpose of this study was to develop an analytical method suitable to confirm and measure the quantity of androsterone from celery root. A LC-MS/MS method was developed using a Turbo V source in positive ionization mode. Analytical parameters such as: linearity, detection and quantification limits, accuracy and precision and matrix effect were evaluated. The calibration curve was developed in the range of 100 to 400 ng/ml with a correlation coefficient r2 of 0.9968 and detection limit of 10 ng/ml. The extraction method was tested for the recovery degree. The recovery obtained was 92.1±2.2%. The method was used to determine the content of androsterone from three celery varieties from Romanian market.